U. S. fourth graders’ ınformational text comprehension: ındicators from NAEP - Mariam Jean Dreher (International Electronic Journal of Elementary Education, 2017)
This study is a secondary analysis of reading data collected from over 165,000 fourth graders as part of the U.S. National Assessment of Educational Progress. Using hierarchical linear modelling, the authors investigated factors associated with students’ informational text comprehension, including out-of-school reading engagement, and in-school measures of cross-curricular reading, discussion about reading, and reading-related activities (e.g., book reports, projects). In addition, this study examined the interactions between these factors, informational text comprehension, and students’ eligibility for Free and Reduced Priced Meals (FARMS). There were positive associations between students’ informational text comprehension and their reading engagement, cross-curricular reading, and discussion about reading. However, reading-related experiences were associated with lower than expected scores. In addition, out-of-school reading engagement and in-school reading experiences may not be associated with informational reading comprehension to the same degree for the most at-risk U.S. students, as most results differed in strength of association for FARMS-eligible students.